2021
DOI: 10.18196/jai.v22i1.9419
|View full text |Cite
|
Sign up to set email alerts
|

Conservatism, Earnings Quality, and Stock Prices - Indonesian Evidence

Abstract: Research aims: This research investigates the association of conservatism (both conditional and unconditional) with quality of earnings as well as with stock prices on companies listed on the Indonesia Stock Exchange (IDX).Design/Methodology/Approach: The research uses a sample of 846 observations of publicly listed companies on the Indonesian Stock Exchange for the fiscal year that ends on December 31, 2016 through 2018. Conditional conservatism is measured by using an asymmetric timeliness measure from Basu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
0
9
0
2
Order By: Relevance
“…Konservatisme akuntansi menjadi satusatunya karakteristik kualitatif yang mencakup persyaratan ini (Neag & Maşca, 2015). Selain itu, konservatisme menjadi salah satu indikator kualitas laba, selain kualitas akrual, prediktabilitas, keberlanjutan, persistensi, ketepatwaktuan, dan ketidakpastian laba (Ahmed, 2020;Krismiaji & Sururi, 2021). Laba dianggap berkualitas tinggi jika laba merupakan prediktor dari laba yang berkelanjutan (future earnings).…”
Section: Pendahuluanunclassified
“…Konservatisme akuntansi menjadi satusatunya karakteristik kualitatif yang mencakup persyaratan ini (Neag & Maşca, 2015). Selain itu, konservatisme menjadi salah satu indikator kualitas laba, selain kualitas akrual, prediktabilitas, keberlanjutan, persistensi, ketepatwaktuan, dan ketidakpastian laba (Ahmed, 2020;Krismiaji & Sururi, 2021). Laba dianggap berkualitas tinggi jika laba merupakan prediktor dari laba yang berkelanjutan (future earnings).…”
Section: Pendahuluanunclassified
“…In addition, unconditional conservatism does not influence the accounting comparability through the first and second factors (the relationship between cash flows and earnings of each share and the relationship between share return and earnings and losses of each share). Penman and Zhang (2002), Elbolok (2011), andDidar et al (2016), have reported similar results. Their findings show that unconditional conservatism has no impact on the quality of reporting.…”
Section: Discussionmentioning
confidence: 63%
“…MB is a measure of unconditional conservatism (Ismail and Elbolok 2011). M represents market value, and B represents book value.…”
Section: Hypothesismentioning
confidence: 99%
“…This is reinforced by research conducted by Sardo et al, (2018), Amin et al, (2018), andAli et al, (2021) which state that conservatism has a positive effect on financial performance. Meanwhile, research Krismiaji & Sururi (2021) states conservatism does not affect financial performance.…”
Section: Hypotheses Developmentmentioning
confidence: 95%